Human serum antibodies against EBV latent membrane protein 1 cross-react with α-synuclein - Woulfe, John; Gray, Madison T.; Ganesh, Munisha S.; Middeldorp, Jaap M. (Université d'Ottawa | University of Ottawa, 2016)
To identify the epitope on α-synuclein (α-syn) to which antibodies against the Epstein-Barr virus (EBV) latent membrane protein 1 (LMP1) bind and to determine whether antibodies targeting this mimicry domain are present in human sera.